1998
DOI: 10.1073/pnas.95.14.8170
|View full text |Cite
|
Sign up to set email alerts
|

Racial variability in the UDP-glucuronosyltransferase 1 ( UGT1A1 ) promoter: A balanced polymorphism for regulation of bilirubin metabolism?

Abstract: A polymorphism in the promoter of the UDPglucuronosyltransferase 1 (UGT1A1) gene has been shown to cause Gilbert syndrome, a benign form of unconjugated bilirubinemia. Promoters containing seven thymine adenine (ta) repeats have been found to be less active than the wild-type six repeats, and the serum bilirubin levels of persons homozygous or even heterozygous for seven repeats have been found to be higher than those with the wild-type six repeats. We have now examined the genotypes in persons of Asian, Afric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

39
601
10
3

Year Published

1999
1999
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 780 publications
(662 citation statements)
references
References 29 publications
39
601
10
3
Order By: Relevance
“…This scenario may be particularly relevant for the UGT1A1*6 variant, which was shown to be associated with reduced bilirubin glucuronidation and higher serum bilirubin levels, a trait previously proposed to have evolved under balancing selection. 15 In the case of the UGT1A3 V47A variant, we inferred that the derived allele is the one that occurs at high frequency in Asians; given the reduced activity associated with this allele, these results imply that either UGT1A3 is a dispensable gene or that the reduced UGT1A3 activity is advantageous in east Asian populations. It was previously proposed that variants in drug-metabolizing enzymes (DMEs) were likely targets of natural selection during the evolution of human populations and underlie human adaptations to different environments and diets.…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…This scenario may be particularly relevant for the UGT1A1*6 variant, which was shown to be associated with reduced bilirubin glucuronidation and higher serum bilirubin levels, a trait previously proposed to have evolved under balancing selection. 15 In the case of the UGT1A3 V47A variant, we inferred that the derived allele is the one that occurs at high frequency in Asians; given the reduced activity associated with this allele, these results imply that either UGT1A3 is a dispensable gene or that the reduced UGT1A3 activity is advantageous in east Asian populations. It was previously proposed that variants in drug-metabolizing enzymes (DMEs) were likely targets of natural selection during the evolution of human populations and underlie human adaptations to different environments and diets.…”
Section: Discussionmentioning
confidence: 80%
“…Hence, the severity of inherited hemolytic syndromes such as glucose 6-phosphate dehydrogenase deficiency and sickle cell anemia may be exacerbated or mitigated by variants of UGT1A and these interactions may have affected the evolutionary history of this gene in different human populations. [13][14][15] While the primary selective pressure for UGT1A enzyme function may have been metabolism of endogenous molecules, UGT1A function is necessary for elimination of exogenous compounds such as the anti-cancer drug irinotecan. [16][17][18] The same common UGT1A1 variants associated with mild elevations of serum bilirubin are associated with diminished in vitro glucuronidation of the active irinotecan metabolite, SN-38, [19][20][21][22] and prolonged exposure and increased toxicity in patients receiving this agent.…”
Section: Introductionmentioning
confidence: 99%
“…Functional studies revealed that increasing the number of repeats in the promoter region leads to a decrease in the rate of transcription initiation of the UGT1A1 gene. 66,[107][108][109] The 'wild-type' allele (UGT1A1*1) contains six TA repeats, whereas the most common variant allele (UGT1A1*28) contains seven TA repeats and is associated with the mild form of the inherited unconjugated hyperbilirubinemia syndrome (Gilbert's syndrome). 109,110 Gilbert's syndrome is also characterized by the absence of liver disease and by episodes of mild intermittent jaundice and is found in approximately 6-12% of the population.…”
Section: Ugt1a1mentioning
confidence: 99%
“…7 Global studies of polymorphisms in UGT1A have shown alleles and genotypes to be unequally distributed among different ethnic human populations across the world. 4,8,9 In the present study, the intra-ethnic difference in allele and haolptype frequencies of polymorphisms in UGT1A1 was examined in three Chinese ethnic populations. In addition, the relationship between the concentrations of total serum bilirubin (T-bil) and haplotype structure of UGT1A1 in healthy people were evaluated.…”
Section: Introductionmentioning
confidence: 99%